The Impact of the Digital Revolution on Health Research: A Bibliometric Review - Loso Judijanto; Sulasmi Anggo; Tyas Putri Utami; Dito Anurogo; Dedah Ningrum (Journal of World Future Medicine, Health and Nursing, 2024)
The digital revolution has had a significant impact on health research. The digital revolution in health refers to the fundamental transformation in the utilization of digital technology to improve aspects of health and medical services. This study aims to evaluate the impact of digital revolution changes on health research with a focus on bibliometric analysis. Another objective was to identify research trends, collaboration patterns, and changes in research methodologies associated with digital technology. The research method involved a bibliometric analysis of the number of health publications related to digital terms such as big data, machine learning, and telemedicine over a period of time. Bibliometric data, such as the number of publications, collaboration between researchers, research topics, and method development, were analyzed quantitatively. The results showed a significant increase in digital health-related publications, as well as cross-disciplinary collaboration and the use of technologies such as big data, machine learning, and image analysis have become dominant trends in research methodologies. The study concluded that the digital revolution has changed the landscape of health research, broadened the scope of research, and accelerated innovations in diagnosis, treatment, and health management. Thus, understanding the impact of this digital revolution is important for health researchers and stakeholders in health policy development. This bibliometric study provides valuable insights into the evolution and implications of the impact of the digital revolution in health research, providing a foundation for further development in this domain.